A filter membrane based on a composite of a nuclear pore membrane and gel perfusion and a preparation method thereof

CN122937655APending Publication Date: 2026-10-20QINGDAO BESLAN SEMICONDUCTOR TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611418724.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有的核孔膜孔径一旦通过刻蚀参数确定即固定不变,无法根据外部环境变化实现智能响应性分离

Benefits of technology

[0040]本申请的有益效果包括但不限于:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention discloses a filter membrane based on a composite of a core-pore membrane and gel perfusion, and its preparation method, belonging to the technical field of membrane preparation methods. The method includes the following steps: (1) irradiating and etching a PET or PC film using heavy ion irradiation to obtain a core-pore membrane; (2) dissolving acrylic acid and / or acrylamide and an initiator in water to obtain a reaction solution, immersing the core-pore membrane in the reaction solution to form a grafted modified layer; (3) dispersing poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles in water to form a dispersion, and perfusing the dispersion into the pores of the core-pore membrane forming the grafted modified layer at 37-45℃ using pressure driving and maintaining the temperature, thus obtaining the final product. This invention constructs a grafted modified layer on the inner wall of the core-pore membrane pores, and then stably composites temperature-sensitive nanogel particles into the pores using pressure driving, resulting in a composite filter membrane with excellent temperature response characteristics and good composite stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a filter membrane based on a composite of a nuclear pore membrane and gel perfusion, and its preparation method, belonging to the technical field of membrane preparation methods. Background Technology

[0002] Membrane separation technology, due to its advantages such as high efficiency, energy saving, and ease of operation, has been widely used in water treatment, food processing, biopharmaceuticals, and chemical separation. In the industrial preparation of porous filter membranes, stretching and phase inversion methods are two of the most core and mature production processes. However, due to the significant randomness in the pore formation process, these two methods cannot achieve precise design and uniform construction of the pore structure, resulting in a wide pore size distribution in the produced filter membranes, which significantly reduces the separation selectivity and retention accuracy of the filter membranes.

[0003] To address the aforementioned issues, nuclear pore membranes have attracted attention due to their unique fabrication principle. Nuclear pore membranes are high-precision microporous membranes characterized by uniform pore size, straight-through channels, and strong controllability, and are widely used in medical, environmental protection, food, and energy fields. However, the pore size of existing nuclear pore membranes remains fixed once determined by etching parameters, making it impossible to achieve intelligent responsive separation based on changes in the external environment.

[0004] To this end, researchers have attempted to graft thermosensitive polymers such as poly(N-isopropylacrylamide) (PNIPAM) onto nuclear pore membranes to impart temperature-responsive properties. Existing technologies mainly employ plasma-induced grafting and surface coating or physical adsorption methods to introduce thermosensitive polymers, but these methods typically modify the surface of the nuclear pore membrane without considering filling the pores of the nuclear pore membrane with thermosensitive gel particles.

[0005] Therefore, developing a method to prepare a filter membrane with good temperature responsiveness by modifying the interior of the filter membrane pores while maintaining a high degree of consistency in the nuclear pore membrane pore structure is of great practical significance and application value. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides a method for preparing a filter membrane based on a composite of a core-pore membrane and gel perfusion. By perfusing a temperature-sensitive gel—poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles—into the core-pore membrane, the temperature-responsive characteristics of the filter membrane are achieved.

[0007] According to the first aspect of this application, this application provides a method for preparing a filter membrane based on a nuclear pore membrane and gel perfusion composite, comprising the following steps: (1) PET or PC films are irradiated with heavy ion irradiation, followed by etching and cleaning to obtain a core pore membrane; (2) dissolving acrylic acid and / or acrylamide and initiator in water to obtain a reaction solution, immersing the nuclear pore membrane in the reaction solution, heating to 60-70℃ for 2-6h to form a grafted modification layer; (3) dispersing poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particles in water to form a dispersion, perfusing the dispersion into the nuclear pore membrane pore of the grafted modification layer of step (2) by pressure driving at 37-45℃ and incubating for 5-6h to obtain the product.

[0008] PET film or PC film can form nanoscale pore size by heavy ion irradiation and etching treatment, and the latent track etching selectivity is excellent, which is an excellent nuclear pore membrane polymer material. The nuclear pore membrane obtained by heavy ion irradiation is used as the substrate in the present application, which ensures the high consistency of the pore size of the filter membrane; by compounding poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particles in the nuclear pore membrane pore, the temperature response function of the filter membrane is realized.

[0009] Before perfusing the poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particles into the nuclear pore membrane pore, a chemical modification layer is first grafted on the inner wall of the nuclear pore membrane pore: the nuclear pore membrane treated by heavy ion irradiation and etching will leave active groups such as peroxide in the pore, and acrylic acid has carboxyl groups and acrylamide has amide groups, which can be decomposed into free radicals by thermal initiation, and then in-situ grafting can be initiated; at the same time, acrylic acid and acrylamide both have carbon-carbon double bonds, which can be polymerized to obtain polyacrylic acid, polyacrylamide or copolymer of the two with abundant carboxyl or amide groups under the action of initiator and thermal initiation. Carboxyl and amide groups can provide active anchor sites, laying a chemical foundation for uniform fixation of subsequent nanogels. In addition, when acrylic acid and acrylamide are included in the reaction solution of step (2), the amide or crosslinking reaction of the two cannot be caused under this reaction condition, so a large number of carboxyl and amide groups can be retained.

[0010] The present application adopts pressure-driven perfusion method, which perfuses nanogel into the nuclear pore membrane pore by pressure driving, and ensures uniform distribution of gel particles in the pore by the chemical anchoring effect of the grafted modification layer, rather than only coating on the membrane surface. The grafted modification layer and poly(N-isopropyl acrylamide-co-acrylic acid) both have abundant hydrogen bonds, which can form a dense hydrogen bond network, thereby giving the gel particles excellent anti-washing ability. The lower critical solution temperature (LCST) of poly(N-isopropyl acrylamide-co-acrylic acid) is about 32℃, and the pressure-driven perfusion at 37-45℃ can realize the volume shrinkage of the gel particles, thereby realizing the smooth perfusion of the gel particles, and the incubation process can ensure that the gel particles can be retained and fixed in the pore by the hydrogen bond interaction with the grafted modification layer, realizing the stability of the compounding.

[0011] Optionally, the particle size of the poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles is 25-35% of the pore size of the nuclear pore membrane.

[0012] The particle size of the nanogel particles is 25-35% of the pore size of the nuclear pore membrane, which can ensure that the gel does not completely block the pore channel when it swells at low temperature, and also does not generate excessive radial swelling stress on the pore channel wall, thereby effectively protecting the long-term integrity of the pore channel structure of the nuclear pore membrane.

[0013] Optionally, the preparation method of the poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles in step (3) is: N-isopropylacrylamide, acrylic acid, crosslinking agent, initiator are dissolved in water to obtain an aqueous solution with a total concentration of N-isopropylacrylamide and acrylic acid of 100-150 mmol / L, and the reaction is carried out at 60-80°C for 4-6h. After the reaction is completed, dialysis purification is performed, and the poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles are obtained.

[0014] The carboxyl groups introduced by copolymerization of N-isopropylacrylamide and acrylic acid can form a more dense multi-point hydrogen bond network between the carboxyl groups and amide groups in the graft modification layer, significantly improving the fixing strength of the gel particles in the pore channel, reducing the risk of falling during oscillation and use, and thereby improving the stability of the filter membrane.

[0015] The adjustment of each parameter in the above preparation method can control the particle size of the prepared poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles to be not too large, ensuring that the particles can be smoothly pressed into the pore channel.

[0016] Optionally, the acrylic acid is 5-15 mol% of the N-isopropylacrylamide.

[0017] With the increase of the amount of acrylic acid added, the particle size of the nanogel particles will show a controllable increasing trend, and the LCST of the polymer will also increase. With the above amount of acrylic acid added, an appropriate amount of carboxyl functional groups can be introduced, and the particle size of the gel particles will not be in an uncontrollable state, and the LCST of the copolymer will not increase too much, resulting in a decrease in the temperature sensitivity of the gel.

[0018] Optionally, the crosslinking agent is N,N'-methylenebisacrylamide.

[0019] Optionally, the amount of the crosslinking agent is 4-8 mol% of the total amount of N-isopropylacrylamide and acrylic acid.

[0020] The amount of crosslinking agent affects the crosslinking density of poly(N-isopropylacrylamide-co-acrylic acid) gel, which in turn affects the volumetric phase transition behavior of the gel. If the amount of crosslinking agent is too low, the crosslinking density will be too low, resulting in low mechanical strength of the gel, making it prone to breakage during subsequent pressure driving. If the amount of crosslinking agent is too high, the crosslinking density will be too high, leading to a reduced phase transition amplitude of the gel and making it difficult to achieve temperature-responsive functionality.

[0021] Optionally, the initiator is ammonium persulfate or potassium persulfate.

[0022] Optionally, the amount of the initiator is 0.5-1 mol of the total amount of N-isopropylacrylamide and acrylic acid.

[0023] The amount of the initiator mentioned above allows the polymerization reaction to proceed at a controllable rate, which is beneficial for obtaining nanogels with uniform particle size.

[0024] Optionally, the thickness of the PET film or PC film is 10-30 μm.

[0025] A thickness range of 10-30 μm ensures that the pores of the subsequently formed nuclear pore membrane have a suitable aspect ratio, allowing the gel dispersion to pass smoothly through the entire pore structure during pressure driving. If the thickness is less than 10 μm, the mechanical strength of the resulting filter membrane will be insufficient; if the thickness is greater than 30 μm, the aspect ratio of the nuclear pore membrane pores will be too large, leading to increased flow resistance during pressure driving and affecting the uniformity of perfusion.

[0026] Optionally, the ion energy of the heavy ion irradiation in step (1) is 5-50 MeV / u, and the irradiation flux is 1×10⁻⁶. 5 -5×10 7 / cm 2 .

[0027] The parameters mentioned above are matched with the thickness of PET or PC films, ensuring that heavy ions have sufficient penetration depth to penetrate the PET or PC films, making the latent track damage area uniform in the film thickness direction, and ensuring that the pore size of the nanopores formed after chemical etching is uniform along the axial direction.

[0028] Optionally, the etching process in step (1) involves immersing the PET or PC film irradiated with heavy ions in a NaOH solution preheated to 80-90°C for 1.5-2 hours.

[0029] The pore inner wall formed under these etching conditions has a suitable density of active groups and surface energy, providing a suitable chemical environment for the subsequent uniform graft polymerization of acrylic acid / acrylamide on the pore inner wall.

[0030] Optionally, the concentration of the acrylic acid and / or the acrylamide in the reaction solution in step (2) is 10-20 wt%.

[0031] The concentration can make the thickness of the formed grafting modification layer moderate, which can provide sufficient active sites and ensure the retention rate of the effective pore size of the channel.

[0032] Optionally, the initiator is ammonium persulfate or potassium persulfate.

[0033] Optionally, the amount of the initiator is 0.5-1 mol% of the acrylic acid and / or the acrylamide.

[0034] Optionally, the concentration of the poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particles in the dispersion in step (3) is 2.5-10 wt%.

[0035] The concentration range can make the nanochannel filled with an appropriate amount of gel particles, which can avoid excessive filling of the gel in the channel to cause complete blockage of the filter membrane at low temperature and loss of the basic flux.

[0036] Optionally, the pressure of the pressure-driven is 0.05-0.2 MPa.

[0037] If the pressure of the pressure-driven is too low, the gel may not be able to effectively enter the channel, and if the pressure is too high, a large amount of gel may penetrate the nuclear pore membrane and accumulate on the surface of the membrane.

[0038] According to a second aspect of the present application, the present application provides a filter membrane based on the combination of a nuclear pore membrane and a gel perfusion, which is prepared by the preparation method of the filter membrane based on the combination of a nuclear pore membrane and a gel perfusion according to any one of the above.

[0039] The filter membrane prepared by the present application is filled with poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particles in the channel, the LCST of poly(N-isopropyl acrylamide-co-acrylic acid) is 32℃, when the environmental temperature is lower than the temperature, the gel molecular chain forms hydrogen bonds with water molecules, the volume swells, the effective filtration pore size is greatly reduced, and the retention of large molecules is realized; when the environmental temperature is higher than the temperature, the hydrogen bonds are broken, the molecular chain is hydrophobic and collapses, the water is discharged, the volume shrinks, and the effective flow space in the channel increases, thereby realizing the temperature response function.

[0040] The beneficial effects of the present application include but are not limited to: 1. The preparation method of the filter membrane based on the combination of a nuclear pore membrane and a gel perfusion according to the present application, the nuclear pore membrane obtained by heavy ion irradiation is used as the substrate, which ensures the high consistency of the pore size of the filter membrane; by combining the poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particle in the channel of the nuclear pore membrane, the temperature response function of the filter membrane is realized.

[0041] 2. The preparation method of the filter membrane based on the composite of nuclear pore membrane and gel perfusion according to the present application, by introducing the grafting modification layer, provides active anchoring sites, and lays a chemical foundation for the subsequent uniform fixation of nanogel.

[0042] 3. The preparation method of the filter membrane based on the composite of nuclear pore membrane and gel perfusion according to the present application, adopts pressure-driven perfusion, drives the nanogel into the pore channel of the nuclear pore membrane by pressure, and ensures the uniform distribution of the gel particles in the pore channel by the chemical anchoring effect of the grafting modification layer.

[0043] 4. The filter membrane based on the composite of nuclear pore membrane and gel perfusion according to the present application, the pore channel is filled with poly (N-isopropyl acrylamide-co-acrylic acid) nanogel particles, which can realize volume swelling or shrinkage according to the environmental temperature, thereby realizing the temperature response function. DETAILED DESCRIPTION

[0044] The present application will be described in detail below with reference to examples, but the present application is not limited to these examples.

[0045] Unless otherwise specified, the raw materials in the examples and comparative examples of the present application are purchased through commercial channels.

[0046] Unless otherwise specified, the methods used in the examples and comparative examples of the present application are conventional methods in the prior art.

[0047] Example 1 The present example relates to a preparation method of a filter membrane based on the composite of nuclear pore membrane and gel perfusion, comprising the following steps: (1) A PET film with a thickness of 10 μm is irradiated by heavy ion irradiation, the ion energy is 5 MeV / u, the irradiation fluence is 1 × 10 5 / cm 2 , after the end, the film is immersed in a NaOH solution (0.5 mol / L) preheated to 80℃ for etching for 2 h, and then repeatedly washed with deionized water to obtain a nuclear pore membrane; (2) Acrylic acid and ammonium persulfate are dissolved in water to obtain a reaction solution with an acrylic acid concentration of 10 wt%, the amount of ammonium persulfate is 0.5 mol% of acrylic acid, the nuclear pore membrane is immersed in the reaction solution, heated to 60℃ and reacted for 6 h to form a grafting modification layer; (3) Poly (N-isopropyl acrylamide-co-acrylic acid) nanogel particles are dispersed in water to form a dispersion liquid with a poly (N-isopropyl acrylamide-co-acrylic acid) nanogel particle concentration of 2.5 wt%, the dispersion liquid is perfused into the pore channel of the nuclear pore membrane with a grafting modification layer formed in step (2) by pressure driving at 37℃ and incubated for 6 h, the pressure is 0.2 MPa, and the product is obtained.

[0048] The preparation method of the poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles is as follows: N-isopropylacrylamide, acrylic acid, N,N'-methylenebisacrylamide and ammonium persulfate were dissolved in water to obtain an aqueous solution with a total concentration of N-isopropylacrylamide and acrylic acid of 100 mmol / L, wherein the concentration of acrylic acid was 5 mol% of N-isopropylacrylamide, the concentration of N,N'-methylenebisacrylamide was 4 mol% of the total amount of N-isopropylacrylamide and acrylic acid, and the concentration of ammonium persulfate was 0.5 mol% of the total amount of N-isopropylacrylamide and acrylic acid. The reaction was carried out at 60°C for 6 h, and then dialysis purification was performed to obtain the product.

[0049] Example 2 The present embodiment relates to a preparation method of a filter membrane based on a nuclear pore membrane and a gel perfusion composite, comprising the following steps: (1) A PC film with a thickness of 30 μm was irradiated by heavy ion irradiation, the ion energy was 50 MeV / u, and the irradiation fluence was 5×10 7 / cm 2 After the irradiation, the film was immersed in a preheated NaOH solution (0.5 mol / L) at 90°C for etching for 1.5 h, and then repeatedly washed with deionized water to obtain a nuclear pore membrane; (2) Acrylamide and potassium persulfate were dissolved in water to obtain a reaction solution with a total concentration of acrylamide of 20 wt%, and the amount of potassium persulfate was 1 mol% of the total amount of acrylamide. The nuclear pore membrane was immersed in the reaction solution and heated to 70°C for 2 h to form a grafted modification layer; (3) The poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles were dispersed in water to form a dispersion liquid with a concentration of 10 wt% of the poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles. The dispersion liquid was perfused into the pore channels of the nuclear pore membrane with the grafted modification layer formed in step (2) by pressure driving at 45°C and incubated for 5 h, and the pressure was 0.05 MPa to obtain the product.

[0050] The preparation method of the poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles is as follows: N-isopropylacrylamide, acrylic acid, N,N'-methylenebisacrylamide and potassium persulfate were dissolved in water to obtain an aqueous solution with a total concentration of N- isopropylacrylamide and acrylic acid of 150 mmol / L, wherein the concentration of acrylic acid was 15 mol% of N-isopropylacrylamide, the concentration of N,N'- methylenebisacrylamide was 8 mol% of the total amount of N-isopropylacrylamide and acrylic acid and the concentration of potassium persulfate was 1 mol% of the total amount of N-isopropylacrylamide and acrylic acid; the reaction was carried out at 80°C for 4 h, and then dialysis purification was performed to obtain the product.

[0051] Example 3 The embodiment relates to a preparation method of a filter membrane based on a nuclear pore membrane and gel perfusion, and comprises the following steps: (1) PET film with a thickness of 20 mu m is irradiated by heavy ion irradiation, ion energy is 30 MeV / u, the fluence of irradiation is 2*10 7 / cm 2 After the end, the film is soaked in a NaOH solution (0.5 mol / L) preheated to 90 DEG C for etching for 1.8 h, and is repeatedly cleaned by deionized water to obtain a nuclear pore membrane; (2) acrylamide and ammonium persulfate are dissolved in water to obtain a reaction solution with an acrylate concentration of 15 wt%, the amount of ammonium persulfate is 0.8 mol% of the total amount of acrylamide, the nuclear pore membrane is soaked in the reaction solution, and heating is conducted to 65 DEG C for reaction for 4 h to form a grafted modification layer; (3) poly (N-isopropyl acrylamide-co-acrylic acid) nanogel particles are dispersed in water to form a dispersion liquid with a poly (N-isopropyl acrylamide-co-acrylic acid) nanogel particle concentration of 6 wt%, the dispersion liquid is perfused into the nuclear pore membrane channel of the grafted modification layer formed in the step (2) by pressure driving at 40 DEG C and is kept for 5.5 h, and the pressure is 0.1 MPa, and the preparation is completed.

[0052] The preparation method of the poly (N-isopropyl acrylamide-co-acrylic acid) nanogel particles is as follows: N-isopropyl acrylamide, acrylic acid, N,N'-methylene bisacrylamide and ammonium persulfate are dissolved in water to obtain an aqueous solution with a total concentration of N-isopropyl acrylamide and acrylic acid of 120 mmol / L, wherein the acrylic acid is 10 mol% of the N-isopropyl acrylamide, the N,N'-methylene bisacrylamide is 6 mol% of the total amount of N-isopropyl acrylamide and acrylic acid, and the ammonium persulfate is 0.7 mol% of the total amount of N-isopropyl acrylamide and acrylic acid; the reaction is carried out at 70 DEG C for 5 h, and the preparation is completed after dialysis purification.

[0053] Example 4 The difference between the embodiment and the embodiment 3 is that acrylic acid and acrylamide with a mass ratio of 1:2 are used to replace acrylamide in the step (2), and the rest are the same.

[0054] Example 5 The difference between the embodiment and the embodiment 3 is that acrylic acid and acrylamine with a mass ratio of 2:1 are used to replace acrylamide in the step (2), and the rest are the sam.

[0055] Example 6 The difference between the embodiment and the embodiment 3 is that the acrylic acid is 20 mol% of the N-isopropyl acrylamide in the preparation method of the poly (N-isopropyl acrylamide-co-acrylic acid), and the rest are the same.

[0056] Example 7 The difference between this example and Example 3 is that the thickness of the PET film in step (1) is 35 μm, and the rest are the same.

[0057] Example 8 The difference between this example and Example 3 is that the concentration of acrylamide in the reaction solution in step (2) is 5 wt%, and the rest are the same.

[0058] Example 9 The difference between this example and Example 3 is that the concentration of acrylamide in the reaction solution in step (2) is 25 wt%, and the rest are the same.

[0059] Example 10 The difference between this example and Example 3 is that the concentration of N-isopropyl acrylamide in the aqueous solution obtained in the preparation method of the poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particles is 180 mmol / L, and the rest are the same.

[0060] Example 11 The difference between this example and Example 3 is that the amount of N,N'-methylenebisacrylamide used in the preparation method of the poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particles is 10 mol% of N-isopropyl acrylamide, and the rest are the same.

[0061] Example 12 The difference between this example and Example 3 is that the concentration of poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particles in the dispersion solution of step (3) is 13 wt%, and the rest are the same.

[0062] Example 13 The difference between this example and Example 3 is that the pressure in step (3) is 0.25 MPa, and the rest are the same.

[0063] Comparative Example 1 The difference between this comparative example and Example 3 is that poly N-isopropyl acrylamide nanogel particles are used instead of poly(N-isopropyl acrylamide-co-acrylic acid) nanogel particles, and no acrylic acid is added in the preparation method of the nanogel particles, and the rest are the same.

[0064] Comparative Example 2 The difference between this comparative example and Example 3 is that there is no step (2), and the rest are the same.

[0065] Comparative Example 3 The difference between this comparative example and Example 3 is that the perfusion temperature in step (3) is 28°C, and the rest are the same.

[0066] Test Example 1 The pore size of the nuclear pore membrane obtained in the above examples and comparative examples and the particle size of the gel particles were tested, and the results are shown in Table 1.

[0067] Table 1

[0068] Test Example 2 The filter membranes obtained in the above examples and comparative examples were respectively installed in a membrane flux test device, and the pure water flux was tested at different temperatures (25℃, 35℃, 45℃), and a stability test was performed: the filter membranes obtained in the above examples and comparative examples were continuously oscillated and soaked in deionized water for 72h, and then the pure water flux was tested at 25℃ (the data in the fifth column in Table 2), and the test results are shown in Table 2.

[0069] Table 2

[0070] According to the data in Table 2, the filter membrane prepared by the scheme of the present application has a lower flux at 25℃ due to the swelling of the gel to block the pores, the flux jumps at 35℃ as the gel begins to shrink, and the flux reaches the highest at 45℃ as the gel fully shrinks, showing excellent temperature response characteristics. The reaction monomers of the grafting modification layer in Examples 4 and 5 are acrylic acid and acrylamide in different mass ratios, and the performance is similar to that of Example 3.

[0071] The increase in the content of acrylic acid in the nanogel particles of Example 6 leads to an increase in the particle size of the gel particles and an increase in the LCST, thereby requiring a higher temperature to achieve shrinkage, and the temperature sensitivity decreases; the increase in the thickness of the PET film in Example 7 leads to uneven distribution of the gel during pressure-driven perfusion, and the gel is insufficiently filled in some pores, resulting in a decrease in the effective blocking rate at low temperature and a decrease in the response amplitude at high temperature; the grafting layer of the filter membrane obtained in Example 8 is too thin, resulting in insufficient anchoring sites and a small amount of gel fixation, and the temperature responsiveness is poor; the grafting layer of Example 9 is too thick to block the pores, resulting in a significant decrease in the flux at each temperature; the nanogel particles obtained in Example 10 are too large, and some cannot enter the pores, but only deposit on the surface, resulting in poor response uniformity; the high cross-linking degree of the gel in Example 11 limits the volume phase transition amplitude of the gel, resulting in poor temperature responsiveness; the excessive filling of the gel in the pores of the filter membrane of Example 12 almost completely blocks the pores at 25℃, and even after shrinking at high temperature, there is still excess gel occupying the space, resulting in a low flux at high temperature; the high pressure of Example 13 causes partial damage to the surface of the filter membrane and the gel is pressed through, resulting in poor temperature responsiveness.

[0072] Comparative Example 1 uses poly (N-isopropylacrylamide) nanogel particles instead of poly (N-isopropylacrylamide-co-acrylic acid) nanogel particles, due to relatively less hydrogen bonds, resulting in a small amount of gel particles deposited on the surface, so that the pure water flux at 25℃ is slightly reduced, but the temperature response ability is not much different from Example 3. Comparative Example 2 has no grafting layer, and the gel can be physically trapped in the channel at the beginning, but most of the gel falls off after 72h, and the response is greatly attenuated. The perfusion temperature of Comparative Example 3 is lower than the LCST, and the gel is in a swollen state, so it cannot be effectively pressed into the inside of the channel, and only a small amount is deposited on the surface, and the temperature response is very weak.

[0073] From the stability test data in Table 2 (the data in the fifth column of Table 2 compared with the data in the second column), it can be seen that the composite stability of the filter membrane obtained by the scheme of the present application is higher, and the flux only increases slightly after 72h of oscillation, indicating that only a small amount of gel falls off.

[0074] Example 6 has good stability between gel particles and grafting modification layer although the particle size of the gel particles increases and the LCST also rises, so the stability test performs well; the increase in the thickness of the membrane of Example 7 causes the gel to be unevenly distributed in the channel during pressure-driven perfusion, and the gel is not firmly anchored on the surface layer and the pore, so part of it falls off after oscillation, and the degree of channel blockage at 25℃ is reduced; the grafting layer of Example 8 is too thin, resulting in a serious lack of anchoring sites, and most of the gel falls off during oscillation, proving the necessity of a concentration range of 10-20wt%; the over-thick grafting layer in Example 9 has significantly reduced the effective inner diameter of the channel, so even if the gel does not fall off, the base flux has been severely limited; the gel particles in Example 10 are too large in size to enter the inside of the channel, and are only deposited on the surface of the membrane, and basically all fall off after oscillation; the high cross-linking degree of the gel in Example 11 makes the internal network more dense and the mechanical strength higher, so it is not easy to break and fall off during oscillation; under the high concentration of gel particles in Example 12, although part of the gel on the outer layer falls off, there is still excess gel firmly stuck in the deep part of the channel, continuously blocking the channel; the high pressure of Example 13 causes part of the gel to be pressed through the membrane surface or damage the grafting layer on the inner wall of the channel, and part of the gel is lost with the fluid.

[0075] Comparative Example 1 uses poly (N-isopropylacrylamide) nanometer gel particles instead of poly (N-isopropylacrylamide-co-acrylic acid) nano-gel particles, and the relative hydrogen bond is less, so the stability of the composite with the grafting modification layer is poor; Comparative Example 2 has no grafting layer, and the gel is only physically trapped in the channel, and most of it falls off after oscillation; the perfusion temperature of Comparative Example 3 is lower than the LCST, so the gel is in a swollen state, the particle size is larger than the pore size of the channel, and it cannot be pressed into the inside of the channel, only a small amount is attached to the surface of the membrane, and basically falls off after oscillation.

[0076] The above merely illustrates the embodiments of the present application, and the protection scope of the present application is not limited to these specific embodiments, but determined by the claims of the present application. The present application can have various changes and modifications for those skilled in the art. Any modification, equivalent replacement, improvement, etc. within the technical thought and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a filter membrane based on a nuclear pore membrane and gel perfusion composite, characterized in that, Includes the following steps: (1) PET or PC films are irradiated with heavy ion irradiation, followed by etching and cleaning to obtain a core pore membrane; (2) Dissolve acrylic acid and / or acrylamide and initiator in water to obtain a reaction solution, immerse the nuclear pore membrane in the reaction solution, heat to 60-70℃ and react for 2-6 hours to form a grafted modified layer; (3) Disperse poly(N-isopropylacrylamide-coacrylic acid) nanogel particles in water to form a dispersion. At 37-45℃, inject the dispersion into the pores of the core pore membrane in step (2) by pressure driving and keep it warm for 5-6 hours to obtain the product.

2. The method for preparing a filter membrane based on a nuclear pore membrane and gel perfusion composite according to claim 1, characterized in that, The particle size of the poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles is 25-35% of the pore size of the nuclear pore membrane.

3. The method for preparing a filter membrane based on a composite of a nuclear pore membrane and gel perfusion according to claim 1, characterized in that, The preparation method of the poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles in step (3) is as follows: N-Isopropylacrylamide, acrylic acid, crosslinking agent, and initiator are dissolved in water to obtain an aqueous solution with a total concentration of 100-150 mmol / L for N-isopropylacrylamide and acrylic acid. The reaction is carried out at 60-80℃ for 4-6 hours, and then purified by dialysis to obtain the final product.

4. The method for preparing a filter membrane based on a composite of a nuclear pore membrane and gel perfusion according to claim 3, characterized in that, The acrylic acid is 5-15 mol of the N-isopropylacrylamide.

5. The method for preparing a filter membrane based on a composite of a nuclear pore membrane and gel perfusion according to claim 3, characterized in that, The crosslinking agent is N,N'-methylenebisacrylamide; The amount of the crosslinking agent is 4-8 mol% of the total amount of N-isopropylacrylamide and acrylic acid. The initiator is ammonium persulfate or potassium persulfate; The amount of the initiator is 0.5-1 mol of the total amount of N-isopropylacrylamide and acrylic acid.

6. The method for preparing a filter membrane based on a composite of a nuclear pore membrane and gel perfusion according to claim 1, characterized in that, The thickness of the PET film or PC film mentioned in step (1) is 10-30 μm.

7. The method for preparing a filter membrane based on a composite of a nuclear pore membrane and gel perfusion according to claim 1, characterized in that, The heavy ion irradiation in step (1) has an ion energy of 5-50 MeV / u and an irradiation flux of 1×10⁻⁶. 5 -5×10 7 / cm 2 ; The etching process described in step (1) involves immersing the PET or PC film irradiated with heavy ions in a NaOH solution preheated to 80-90°C for 1.5-2 hours.

8. The method for preparing a filter membrane based on a composite of a nuclear pore membrane and gel perfusion according to claim 1, characterized in that, The concentration of acrylic acid and / or acrylamide in the reaction solution in step (2) is 10-20 wt%; The initiator is ammonium persulfate or potassium persulfate; The amount of the initiator is 0.5-1 mol of the acrylic acid and / or acrylamide.

9. The method for preparing a filter membrane based on a nuclear pore membrane and gel perfusion composite according to claim 1, characterized in that, The concentration of poly(N-isopropylacrylamide-co-acrylic acid) nanogel particles in the dispersion in step (3) is 2.5-10 wt%; The pressure of the pressure drive is 0.05-0.2 MPa.

10. A filter membrane based on a composite of a nuclear pore membrane and gel perfusion, characterized in that, The filter membrane was prepared using the method described in any one of claims 1-9, which is based on a composite of a nuclear pore membrane and gel perfusion.